Assessing distortion in modified listening scopes (Genser et al., 2025) - Nicole Genser (20648022) (2025)
Purpose: The use of traditional (i.e., unmodified) listening scopes for hearing aid and assistive listening device checks is not practically accessible for all clinicians; such is the case for deaf audiologists. Despite the need, there is a paucity of evidence-based information regarding modified listening scopes. The focus of this investigation was to evaluate the output clarity through various modified listening scopes via a measure of distortion. The impact of hearing aid type on measurements was also preliminarily analyzed. Method: Eight test hearing aids were measured under seven listening scope conditions. A distortion analysis was performed for each setup across 13 frequencies from 250 through 4000 Hz on the Verifit2. Data were analyzed using repeated-measures analysis of variance with within-subject factors to establish internal consistency and agreement between measurements and identify any main effects. Results: Significant main effects of listening scope condition and frequency were observed. There were no effects of trials, suggesting data homogeneity and that hearing aid type did not impact measures. Post hoc analyses indicated that the modified scope utilizing Bluetooth technology generated the most significant distortion in the output of the tested hearing aid. Conversely, distortion from other scopes seems clinically negligible. Conclusion: The findings regarding output clarity of various modified listening scopes have clinical applications for those professionals who find traditional listening scopes practically inaccessible and seek to make evidence-based decisions about using modifications. Supplemental Material S1. No scope condition: distortion output by frequency per trial. Supplemental Material S2. Unmodified scope condition: Distortion output by frequency per trial. Supplemental Material S3. Mold-over-mic condition: Distortion output per frequency by trial. Supplemental Material S4. DM system scope condition: Distortion output by frequency per trial. Supplemental Material S5. Bluetooth scope condition: Distortion output by frequency per trial. Supplemental Material S6. Induction loop scope condition: Distortion output by frequency per trial. Supplemental Material S7. Tube-in-bore scope condition: distortion output by frequency per trial. Supplemental Material S8. Mean distortion output by listening scope condition at 250 hz. Supplemental Material S9. Mean distortion output by listening scope condition at 315 hz. Supplemental Material S10. Mean distortion output by listening scope condition at 400 hz. Supplemental Material S11. Mean distortion output by listening scope condition at 500 hz. Supplemental Material S12. Mean distortion output by listening scope condition at 630 hz. Supplemental Material S13. Mean distortion output by listening scope condition at 800 hz. Supplemental Material S14. Mean distortion output by listening scope condition at 1000 hz. Supplemental Material S15. Mean distortion output by listening scope condition at 1250 hz. Supplemental Material S16. Mean distortion output by listening scope condition at 1600 hz. Supplemental Material S17. Mean distortion output by listening scope condition at 2000 hz. Supplemental Material S18. Mean distortion output by listening scope condition at 2500 hz. Supplemental Material S19. mean distortion output by listening scope condition at 3150 hz. Supplemental Material S20. Mean distortion output by listening scope condition at 4000 hz. Genser, N., Atcherson, S., Wambacq, I., Kagan-Weitz, E., Rooney, A., & McInerney, M. (2025). Assessing distortion in modified listening scopes for deaf audiologists. Perspectives of the ASHA Special Interest Groups, 10(6), 1780–1798. https://doi.org/10.1044/2024_PERSP-24-00181